Model-Model dalam Pengembangan Kurikulum: Analisis Teori, Implementasi, dan Integrasi Pada Konteks Pendidikan di Indonesia - Devy Habibi Muhammad; Siti Maimunah; Habibatul Fitria; Choirun Nisak (CV. Lentera Literasi Indonesia, 2026)
Curriculum development is a key component of the education system, determining the direction, quality, and relevance of learning. An effective curriculum must be able to adapt to student needs, global demands, and local contexts. This study reviews various curriculum development models, including the Tyler, Taba, and CIPP models, and discusses their strengths, weaknesses, and applications in Indonesia. The method used is a qualitative literature review with a descriptive-comparative approach. The analysis examines the basic principles, implementation processes, and evaluation of each model. The results show that each model has unique strengths: the Tyler model emphasizes systematic learning objectives, the Taba model emphasizes teacher participation and local adaptation, while the CIPP model emphasizes continuous evaluation and curriculum improvement. This study emphasizes the importance of integrating the three models to produce an adaptive, contextual, and sustainable curriculum that can support the implementation of the Independent Curriculum in Indonesia. These findings are expected to guide curriculum developers, teachers, and education policymakers in designing and evaluating relevant and high-quality curricula.